Small-scale fisheries management [ frameworks and approaches for the developing world - Andrew, Neil; Pomeroy, R. S. [ (Robert S.)] (CABI, 2011)
Small-scale fisheries make up a large proportion of world's fisheries, both by catch and participation. Covering social and economic aspects of the fishery management and governance challenge, this book provides guidance on innovative and alternative mnagement measures and methods for small-scale fisheries